Inflammatory pseudotumor of the posterior mediastinum- A report of 2 cases - Chadha Kirti; Lila Kunjal; Gala Roshani (Wolters Kluwer Medknow Publications, 2022)
Mediastinal masses span a wide histopathological spectrum. Inflammatory pseudotumors are rare and most commonly described in the lungs but these are reported in almost all the organs in the body. Mediastinal involvement is rare and difficult to diagnose. Clinical manifestations and laboratory investigations and radiology are non-specific. Histomorphology and Immunohistochemistry provide a valuable aid. Complete resection usually provides definitive diagnosis and is treatment of choice.